Nuutsih: interpretation of Celuk village revival via soundscape as a cultural phenomenon - Ni Nyoman Srayamurtikanti; Bambang Sunarto (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2022)
This article discusses the process of creating a work of performing arts entitled "Nuutsih" as an artistic interpretation of cultural phenomena and social phenomena that occur in Celuk Village. Celuk Village is the centre of silver handicrafts in Bali. The village that culturally colours life and economy in Bali experienced a fluctuating event due to the community's attitude towards local wisdom. The local wisdom is in the form of a soundscape in producing silver handicraft motif designs characteristic of Celuk village. This article aims to report on creative activities in creating Nuutsih's musical works. The writing method is an informative reflection of the creative activity the author undertakes as an artist. This method ultimately produces a picture of the artist's creative process in developing a strategy for creating artwork. Mainly with the object of the phenomenon of cultural sounds and the attitude of life of the Celuk village community. The artist sees this object from the perspective of restoring the collective memory of a happy community. Another result is the birth of Nuutsih ontology which will appear described in the discussion of this article. The significance of this article is to demonstrate the application of the rules that artists must adhere to in the creative process of art creation to produce works that the audience can enjoy